Conhecimento, dialética, analogia e identidade na biologia de Aristóteles - Ferigolo, Jorge (Universidade do Vale do Rio dos Sinos, 2012)
Our main purpose in this work is to show that Aristotle developed his biology on the basis of his dialectic method. Demonstration is not the method of biology for several reasons, among them because organisms and their parts can be otherwise than they are; as well as the fact that Aristotle himself observed that mathematical accuracy is not to be demanded except in things which do not contain matter. Since animals are investigated by dialectic, excepted from principles of each area, we can only have common opinions (endoxa) about them, obtained through concepts, methods and arguments, as set out in the Topica. His starting point is the available endoxa or, in the absence of these ones, his own observations of phainomena, as is so often the case in the field of biology. After collecting the available data, Aristotle compares all them each other, observes phainomena, compares the endoxa with each other and with his own observations, resolves any existing problems, tries to reconcile the endoxa, then comes to a conclusion. When there is no prior endoxon, Aristotle compares data culled from his own observations, which consist of real experiments which he himself had carried out. In biology the major concepts are those of comparison, likeness and difference, and more or less, which contributed to the development of other concepts, including identity and analogy. Parts of animals which are to be investigated must first of all be compared each other, in order to determine whether they can be considered to be morphologically identical, or only functionally analogous. These concepts are also important to distinguish predicables, including their topoi. The dialectic method consists of a number of procedures, including comparative, empirical, and descriptive methods, as well as the inductive and the properly called dialectical arguments. In biology identity is not in number but in genus, when it can also be identical in species. Thanks to these concepts, Aristotle formulated several principles, all of which were essential to develop the concept of natural group, among them the general body plan, the principle of correlation of parts, and a law of embryology according to which generic attributes emerge before than the specific ones, during development. Once the natural groups had been recognized, Aristotle already had a taxonomy at his disposal, which did not give priority to function (as has been suggested), but emphasizes morphology. It is untrue that he did not distinguish clearly between homologies (identities) and analogies. The fact is that, sometimes, what nowadays is interpreted as a case of homology was considered (albeit erroneously) by Aristotle to be an analogy, and vice versa. Indeed was Aristotle who first used the concept of analogy in the investigation of nature, to indicate the presence of common functions or properties. Differently from identities, which are used in the process of identification of genera and species, analogies only allow to discriminate genera. Except from genus and species which are eternalized by form, biology is not necessarily true knowledge to Aristotle. As far as causes are concerned, they seem much more evident in biology than in other areas of Aristotles investigation.Formal and final causes are related to the functions of the organs and their parts; so that what is called teleology in biology is actually what is today understood as physiology. Matter as genus in the definition is the relatively indeterminate matter, which has a potential to be determinate by form. The efficient cause of all viscera is the heart, which is anterior to them from a logical and a temporal point of view. Aristotles major contribution to biology does not reside in the empirical content of his work, but rather in the development of several concepts, as well as the dialectic method, to be applied to biology. On the other side, some dialectic procedures are used in many areas of investigation until today, as is the case of the comparative method. Biology as well the methods used by Aristotle have many similarities with today biology, from the collecting of endoxa to the conclusion. Aristotle‟s biology and philosophy have a very close relationship, specially concerning matter and form, theory of causes and theory of act and potency. During embryonary development there is a progressive actualization of form, from the egg and embryo until the adult individual, when the animal is apt to reproduce, which is the actualization of its potential towards a full being.
Keywords: Aristóteles; Filosofia da biologia; Dialética; Aristotle; Philosofy of biology; Dialetics; ACCNPQ::Ciências Humanas::Filosofia